Effects of varying blood flow rate during peripheral veno-arterial extracorporeal membrane oxygen (V-A ECMO) on left ventricular function measured by two-dimensional strain - Ng, Pauline Yeung; Ma, Tammy Sin Kwan; Ip, April; Fang, Shu; Li, Andy Chak Cheung; Wong, Alfred Sai Kuen; Ngai, Chun Wai; Chan, Wai Ming; Sin, Wai Ching (Frontiers in Cardiovascular Medicine, 2023)
Background We evaluated the effects of varying blood flow rate during peripheral veno-arterial extracorporeal membrane oxygen (V-A ECMO) on left ventricular function measured by two-dimensional strain. Methods Adult patients who were supported by peripheral V-A ECMO were recruited. Serial hemodynamic and cardiac performance parameters were measured by transthoracic echocardiogram within the first 48 h after implementation of V-A ECMO. Measurements at 100%, 120%, and 50% of target blood flow (TBF) were compared. Results A total of 54 patients were included and the main indications for V-A ECMO were myocardial infarction [32 (59.3%)] and myocarditis [6 (11.1%)]. With extracorporeal blood flow at 50% compared with 100% TBF, the mean arterial pressure was lower [66 ± 19 vs. 75 ± 18 mmHg, p < 0.001], stroke volume was greater [23 (12–34) vs. 15 (8–26) ml, p < 0.001], and cardiac index was higher [1.2 (0.7–1.7) vs. 0.8 (0.5–1.3) L/min/m2, p < 0.001]. Left ventricular contractile function measured by global longitudinal strain improved at 50% compared with 100% TBF [−2.8 (−7.6- −0.1) vs. −1.2 (−5.2–0) %, p < 0.001]. Similarly, left ventricular ejection fraction increased [24.4 (15.8–35.5) vs. 16.7 (10.0–28.5) %, p < 0.001] and left ventricular outflow tract velocity time integral increased [7.7 (3.8–11.4) vs. 4.8 (2.5–8.5) cm, p < 0.001]. Adding echocardiographic parameters of left ventricular systolic function to the Survival After Veno-arterial ECMO (SAVE) score had better discriminatory value in predicting eventual hospital mortality (AUROC 0.69, 95% CI 0.55–0.84, p = 0.008) and successful weaning from V-A ECMO (AUROC 0.68, 95% CI 0.53–0.83, p = 0.017). Conclusion In the initial period of V-A ECMO support, measures of left ventricular function including left ventricular ejection fraction and global longitudinal strain were inversely related to ECMO blood flow rate. Understanding the heart-ECMO interaction is vital to interpretation of echocardiographic measures of the left ventricle while on ECMO.